The place of the school in the processo f social reproduction: readings of Dukheim, Althusser and Bourdieu (Research, Society and Development, 2023)
Currently, we still hear speeches in the media that claim education and the school as an institution with the potential and task of “transforming” society. Seeking to problematize this discourse commonly overheard among social actors when referring to the function of education, that the school in contemporary society would have the capacity and objective of "transforming" society, this article proposes to analyze, in the light of the contributions left by classic authors of the Sociology of Education such as Émile Durkheim, Louis Althusser and Pierre Bourdieu, how the school institution is closer to functioning as a mechanism for reproducing the unequal conditions of capitalist society than its opposite. The research methodology used will consist of the historical analysis of the studied authors, through bibliographical research. To corroborate Bourdieu's more contemporary contributions, we bring a brief sociological analysis of the role of the school in the process of social reproduction to Jessé de Souza's analysis. Analyzing how a dialogue can be established between the authors selected in this article, we seek to think about the school institution as it is disposed of in concrete reality in the perception of the authors discussed here, who highlight the reproductive dimension of the school system. We do not want to discredit the transformative possibility of the school, but to show how, since its inception, the school has been closer to a conservation trend.